2017
DOI: 10.1007/s12529-017-9652-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Light-to-Moderate Alcohol Consumption to Glucose Metabolism and Insulin Resistance in Nondiabetic Adults: the Moderating Effects of Depressive Symptom Severity, Adiposity, and Sex

Abstract: Purpose We examined the relation of alcohol consumption to glucose metabolism and insulin resistance (IR) as a function of depressive symptoms, adiposity, and sex. Method Healthy adults (aged 18–65 years) provided fasting blood samples and information on lifestyle factors. Alcohol intake was categorized as never, infrequent (1–3 drinks/month), occasional (1–7 drinks/week), and regular (≥2 drinks/day) drinkers. The Beck Depression Inventory (BDI) was used to assess symptom severity. Primary out-comes were fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Habit of alcohol drinking was categorized as regular (1 or more drinks per day), occasional (not every day), and never (no drink at all). 18 , 19 “Sexual life” was defined as the penetration of the penis into the vagina; “partner time” was defined as subjects and sexual partners spending time together instead of alone; and “intimacy behavior” was defined as holding hands, hugging, and kissing.…”
Section: Methodsmentioning
confidence: 99%
“…Habit of alcohol drinking was categorized as regular (1 or more drinks per day), occasional (not every day), and never (no drink at all). 18 , 19 “Sexual life” was defined as the penetration of the penis into the vagina; “partner time” was defined as subjects and sexual partners spending time together instead of alone; and “intimacy behavior” was defined as holding hands, hugging, and kissing.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence provides that low‐to‐moderate alcohol consumption reduces the risk of developing hypertension (Briasoulis, Agarwal, & Messerli, 2012; Taylor et al, 2009). A J‐shaped relationship exists between alcohol consumption and insulin resistance; light‐to‐moderate alcohol consumption decreases insulin production, and heavy drinking increases insulin resistance (Suarez, Beckham, & Green, 2017; Tatsumi et al, 2018). Furthermore, alcohol consumption has a positive association with high‐density lipoprotein (HDL) levels (Vidot et al, 2016); Du, Bruno, Dwyer, Venn, & Gall, 2017), and triglycerides (Foerster et al, 2009; Klop, Rego, & Cabezas, 2013).…”
Section: Alcohol Consumption Ald and The Risk Of Metabolic Syndromementioning
confidence: 99%
“…Regarding alcohol consumption, the opinions are more varied. Some studies have found light-to-moderate alcohol consumption may be beneficial for heart disease, diabetes, or nonalcoholic fatty liver disease (NAFLD), but such findings have not been demonstrated universally [22][23][24]. Interestingly, a human epidemiological study found that compared with lifelong abstainers, individuals who consumed <5, <15, and <30 g EtOH per day exhibited adjusted relative risks of developing T2DM of 0.8, 0.67, and 0.42, respectively [25].…”
Section: Introductionmentioning
confidence: 99%